A combined thermo-mechanical drilling technology for deep geothermal and hard rock reservoirs. (May 2020) - Rossi, Edoardo; Jamali, Shahin; Wittig, Volker; Saar, Martin O.; Rudolf von Rohr, Philipp
Highlights: A novel technology to facilitate hard rock drilling is demonstrated in the field Flame assistance enhances rock mechanical removal by up to a factor of three A thermal assistance is implemented in a conventional drilling system Feasibility of thermal spallation proved through acoustic monitoring Ease of integration in conventional drilling to increase overall performance Abstract: Combined thermo-mechanical drilling is a novel technology to enhance drilling performance in deep hard rock formations. In this work, we demonstrate this technology in the field by implementing the concept on a full-scale drilling rig, and we show its feasibility under realistic process conditions. We provide evidence that the novel drilling method can increase the removal performance in hard rocks by up to a factor of three, compared to conventional drilling methods. From the findings of this work, we conclude that integration of thermal assistance to conventional rotary drilling constitutes an interesting approach to facilitate the drilling process, and therefore increase the access viability to deep georesources in hard rocks.